Critical storytelling : multilingual immigrants in the United States - Pentón Herrera, Luis Javier; Tính Trịnh, Ethan (Critical storytelling, 2021)
"This edited book is a beautiful and powerful collection of poems and personal and visual narratives of multilingual immigrants in the United States. The purpose of this book is to create a space where immigrant stories can be told from their personal perspectives. The contributors are immigrants from all walks of life who represent a diverse picture of languages, professions, and beliefs from the immigrant diasporas within the United States. Inspired by the use of autoethnography, authors examine their own lives through poems and personal and visual narratives to share with others who might have similar experiences. Contributors are: Gabriel Teodoro Acevedo Velázquez, Fatmeh Alalawneh, Bashar Al Hariri, Rajwan Alshareefy, Ana Bautista, May F. Chung, Zurisaray Espinosa, Manuel De Jesús Gómez Portillo, Jamie Harris, Ben Haseen, Lydiah Kananu Kiramba, Babak Khoshnevisan, Sharada Krishnamurthy, Judith Landeros, Jiyoon Lee, Pablo Montes, Aracelis Nieves, Gloria Park, Mauricio Patrón Rivera, Luis Javier Pentón Herrera, Tairan Qiu, R. Joseph Rodríguez, Cristina Sánchez-Martín, Sandy Tadeo, Ethan Tính Trịnh, Geovanny Vicente Romero, and Polina Vinogradova"--